Sharing talk, sharing cognition: philosophy with children as the basis for productive classroom interaction - Laura Kerslake; Sarah Rimmington (Problemy Wczesnej Edukacji)
Taking the linguistic turn requires an examination of the relationship between thought and language: starting with Wittgenstein, we draw out the implications of expressing thought in a jointlyconstructed system of meaning. We then examine the relationship between thought and language in a pedagogical context by drawing on the practice of philosophy with children in the classroom, identifying key skills which are important in the development of meaningful classroom interaction, connecting this to philosophy with children practice. We go on to explore the consequences of educational attainment for those children who enter school with impoverished language, referring to a number of key studies, including our own, which highlight the detrimental effects not only on children’s outcomes at school, but also their ability to become equal inhabitants of a linguistic space. Therefore we argue that a focus on oracy skills crucially underpins wider outcomes. We conclude by looking at ways in which oracy skills can be developed in the classroom, arguing that although there are other techniques for developing oracy skills in the classroom, philosophy with children provides the most comprehensive way of doing this.